2014
DOI: 10.1111/jphp.12185
|View full text |Cite
|
Sign up to set email alerts
|

Comparative oral bioavailability of geniposide following oral administration of geniposide, Gardenia jasminoides Ellis fruits extracts and Gardenia herbal formulation in rats

Abstract: The conclusion reveals that herbal ingredient-ingredient or herb-herb interaction may affect the oral absorption of geniposide-related herbal formulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 19 publications
0
21
0
Order By: Relevance
“…It is known that some dietary phytochemicals are poorly absorbed and the bioavailability of ingested bioactive food compounds is a complex and challenging process (Rein et al, 2013). Interestingly, some studies showed that the bioavailability of a single bioactive compound is much poorer than it is consumed with the whole plant extract (Cheng, Lin, Lin, & Tsai, 2014;Keung, Lazo, Kunze, & Vallee, 1996;Vissers, Bozonet, Pearson, & Braithwaite, 2011), suggesting that the consumption of whole herbal tea may show a greater bioavailability than that of saponins alone. The potential synergistic effects of saponins and other phytonutrients on gut microbiota would be of interest for further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that some dietary phytochemicals are poorly absorbed and the bioavailability of ingested bioactive food compounds is a complex and challenging process (Rein et al, 2013). Interestingly, some studies showed that the bioavailability of a single bioactive compound is much poorer than it is consumed with the whole plant extract (Cheng, Lin, Lin, & Tsai, 2014;Keung, Lazo, Kunze, & Vallee, 1996;Vissers, Bozonet, Pearson, & Braithwaite, 2011), suggesting that the consumption of whole herbal tea may show a greater bioavailability than that of saponins alone. The potential synergistic effects of saponins and other phytonutrients on gut microbiota would be of interest for further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Various chromatographic methods have been published for the determination of GE or GP in combination with other compounds in the biological matrix using HPLC‐UV or LC–MS/MS (Chen et al, ; Cheng, Lin, Lin, & Tsai, ; He et al, ; Hu et al, ; Huang et al, ; Peng et al, ; Qu et al, , ; Wang et al, ). Some methods have been established for simultaneous quantification of GE and GP.…”
Section: Introductionmentioning
confidence: 99%
“…In order to determine the concentration of GE, Caco-2 cells were incubated with a series of GE concentrations (1,2,5,10,25,50,100,200 µg/mL) at 37 ˚C with different durations (6,12,24,48 h). The survival rate of Caco-2 cells at different concentrations of GE was examined.…”
Section: Cytotoxicity Assaymentioning
confidence: 99%
“…The pharmacokinetics, bioavailability and tissue distribution of GE has been reported, and low oral bioavailability limits its clinical application [6,7] . The study of intestinal absorption of drugs can provide important informations such as absorption mechanism, absorption site and factors affecting absorption, and provide reference for drug development [8,9] .…”
Section: Introductionmentioning
confidence: 99%